Carleman estimates for Baouendi–Grushin operators with applications to quantitative uniqueness and strong unique continuation. Issue 10 (3rd July 2022) - Banerjee, Agnid; Garofalo, Nicola; Manna, Ramesh
ABSTRACT: In this paper, we establish some new L 2 − L 2 Carleman estimates for the Baouendi–Grushin operators B γ, in Equation (1). We apply such estimates to obtain: (i) an extension of the Bourgain–Kenig quantitative unique continuation and (ii) the strong unique continuation property for some degenerate sublinear equations.